2017
DOI: 10.3389/fimmu.2017.01053
|View full text |Cite
|
Sign up to set email alerts
|

PRINS Non-Coding RNA Regulates Nucleic Acid-Induced Innate Immune Responses of Human Keratinocytes

Abstract: Cytosolic DNA fragments are recognized as pathogen- and danger-associated molecular patterns that induce a cascade of innate immune responses. Moreover, excessive cytosolic DNA can enhance chronic inflammation, predominantly by activating inflammasomes, and thereby contributing to the pathogenesis of chronic diseases, such as psoriasis. Psoriasis associated non-protein coding RNA induced by stress (PRINS) is a long non-coding RNA, which has been shown to be associated with psoriasis susceptibility and cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 37 publications
0
26
1
Order By: Relevance
“…Previously, we reported that Der p did not trigger the phosphorylation of IκBα, while poly I:C, which is structurally similar to double‐stranded RNA, did . In addition, TLR9 responds to single‐stranded DNA . No phosphorylation of IκBα was observed in keratinocytes treated with or without heparinoid in this study.…”
Section: Discussioncontrasting
confidence: 47%
“…Previously, we reported that Der p did not trigger the phosphorylation of IκBα, while poly I:C, which is structurally similar to double‐stranded RNA, did . In addition, TLR9 responds to single‐stranded DNA . No phosphorylation of IκBα was observed in keratinocytes treated with or without heparinoid in this study.…”
Section: Discussioncontrasting
confidence: 47%
“…The study was approved by the Human Investigation Review Board of the University of Szeged (PSO-EDAFN-002, 23 February 2015, Szeged, Hungary) and complying with the ethical standards in accordance with the Helsinki Declaration. NHEK cells were isolated from the skin samples as described earlier ( 24 ). For ex vivo organotypic skin models (OSMs), 6 mm punch biopsies were washed first with normal saline solution (NSS) containing 2% AB/AM, followed by a wash in AB/AM-free NSS.…”
Section: Methodsmentioning
confidence: 99%
“…The genes transcribed within a 100 kb window upstream or downstream of lncRNAs were considered as potential cis target genes [79]. The second algorithm was used to identify potential trans targets based on RNA sequence complementarity (mRNA-lncRNA) and RNA duplex energy prediction [80,81]. Based on the RNA duplex energy (Free energy < − 50) assessed by RIsearch algorithms [82], the differentially expressed genes and lncRNAs were considered as potentially involved in trans-interaction.…”
Section: Target Gene Prediction and Functional Analysis Of Lncrnasmentioning
confidence: 99%